2003
DOI: 10.1063/1.1569400
|View full text |Cite
|
Sign up to set email alerts
|

Development of a five-band multi-spectral infrared radiometer for low temperature measurements

Abstract: A five-band infrared radiometer has been developed for the measurement of spectral radiance and radiance temperature at low temperatures. The optical system of this radiometer consists of a scanning plane reflecting mirror, five narrow-band interference filters in the 6–12 μm band, a mirror-type rotating chopper, a cold source, a hot source, and a HgCdTe semiconductor detector. Measurement of radiance temperature and spectral radiance using this radiometer is carried out automatically using a personal computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…These results demonstrate a relative SSE of 4 10 3 − × within a 25 mm diameter source and indicate that SSE correction ≤ 3mK at 75º C. To test the measurement reproducibility, the same high quality waterbath BB was used twice: as a reference and as a unit under test with T = 50.073 C. The second high quality waterbath blackbody was used as another reference with a temperature 23.00º C [11]. The temperature of the first water bath BB was measured by the TFC and a platinum resistance thermometer (PRT).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…These results demonstrate a relative SSE of 4 10 3 − × within a 25 mm diameter source and indicate that SSE correction ≤ 3mK at 75º C. To test the measurement reproducibility, the same high quality waterbath BB was used twice: as a reference and as a unit under test with T = 50.073 C. The second high quality waterbath blackbody was used as another reference with a temperature 23.00º C [11]. The temperature of the first water bath BB was measured by the TFC and a platinum resistance thermometer (PRT).…”
Section: Resultsmentioning
confidence: 80%
“…Alternatively, there is another approach to the calibration of a near ambient BB based on relative measurements [2,3,4]. For calibration purposes, two blackbodies of known temperature and emissivity are used and the system response function is calculated.…”
Section: Intoductionmentioning
confidence: 99%
“…4, it is shown that the radiometer output voltage greatly depends on the set temperature of the blackbody source and the spectral channel, which can be explained by a few dominant factors including the wavelength dependence of the spectral transmittance of each optical filter, the numbers of neutral density filters, the spectral responsivity of the detector, and the spectral radiance of the blackbody source. 16 For example, the curves of SW seem like moving the curves of MW right by a distance, which means the trend of SW and MW is similar, but the voltage of MW is larger than the voltage of SW at the same temperature. This is mainly because the wavelength dependence of the spectral transmittance of each optical filter and the spectral responsivity of the detector.…”
Section: Radiometer Calibrationmentioning
confidence: 97%
“…The radiometric characterization of the BB was performed using the tunable-filter comparator (TFC), which is based on relative radiance measurements [11][12][13]. Two reference blackbodies of known temperature and emissivity are used for calculation of the system response function.…”
Section: Tunable-filter Comparatormentioning
confidence: 99%